Pengaruh Pemberian Tepung Daun Lamtoro (Leucaena Leucocephala) Dalam Ransum Terhadap Performan Burung Puyuh Jantan (Coturnix- Coturnix Japonica ) - Sitorus, Tunggul Ferry; Malau, Ester Angriani (LPPM Universitas HKBP Nommensen, 2022)
This study aims to determine the effect of giving lamtoro leaf flour (Leucaena leucocephala) on the performance of male quail (Coturnix-coturnix japonica) aged 2-8 weeks. This research was conducted in the experimental field of the Faculty of Animal Husbandry, HKBP Nommensen University in Simalingkar A Village, Pancur Batu District, Deli Serdang Regency. The research data collection took place for 8 weeks starting from October to December 2021. The experimental design used in this study was a Completely Randomized Design (CRD) with 5 treatments, namely the level of giving lamtoro leaf flour in the ration P0(0%), P1( 1.5%), P2(3%), P3(4.5%), P4(6%), where each treatment was repeated four (4) times and each treatment consisted of 10 male quails. Parameters observed were ration consumption, daily body weight gain, and ration conversion. From the results of the study, it was found that the average consumption of quail rations fed with lamtoro leaf meal for 8 weeks of the study was 9.44 grams/head/day with a range of 9.32 – 9.70 grams/head/day. The average body weight gain of quail was 1.64 grams/head/day with a range of 1.53-1.75 grams/head/day. The average conversion rate for quail was 5.11 with a range of 4.75 -5.39. The results of the variance study (ANOVA) showed that the treatment of giving lamtoro leaf flour in male quail rations had a very significant effect (P<0.01) on daily body weight gain and ration conversion, but had a significant effect (P<0.05) on ration consumption. Based on the results of this study, it is suggested that the best lamtoro leaf flour can be given at the level of 1.5% to 3%.